Increasing vaname shrimp farming efficiency and profitability through IoT and solar-powered Automatic Shrimp Feeder implementation in intensive aquaculture systems - Komalasari, Ria; Anwar, Kasful; Panggabean, Donwill; Setiaji, Agung (Aurelia Journal, 2026)
Feed is the largest contributor to operational costs (50-60%) in intensive vaname shrimp (Litopenaeus vannamei) cultivation, so inefficient feed management can substantially erode profitability. This case study aims to analyze the technical and economic impact of the implementation of an Automatic Shrimp Feeder (ASF) integrated with Internet of Things (IoT) technology and powered by solar energy on PT's intensive shrimp ponds. Mina Balng Berkah, Sukabumi. The research uses mixed methods with qualitative descriptive analysis. The results show that ASF adoption has a significant positive impact. Feed efficiency increased sharply, as indicated by a decrease in the Feed Conversion Ratio (FCR) from 1.5 to 1.25. Apart from that, the use of ASF also has an impact on increasing the Survival Rate (SR) and cultivation productivity. From an economic aspect, feed efficiency and reduced labor requirements for feeding (from 3 to 2 people per cycle) result in reduced operational costs and increased production value, which leads to an increase in net profitability of more than twofold. The application of ASF based on IoT and solar energy has proven to be the optimal solution for achieving precision aquaculture, increasing resource efficiency, and being effective in increasing the productivity and sustainability of shrimp farming.